PENINGKATAN PRESTASI BELAJAR DENGAN METODE MC KERNAN PADA SISWA SMP MUHAMMADIYAH 5DI MAKASSAR TAHUN PELAJARAN 2017/2018 (SUATU STUDI TINDAKAN KELAS) - Sabia Sabia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study is the application of Bandura theory (1978) that human resources are developed through the ability of action and treatment that makes human resources achieve an achievement. Classroom action research is a scientific research activity performed rationally, systematically and empirically reflective on the various actions undertaken by teachers who as well as researchers. This research hopes that the teacher can improve the learning process through a deep study of what happened in his class. The teacher at SMP Muhammadiyah 5 Makassar is no longer a practitioner, who has been satisfied with his work for years without any improvement and innovation, but also as a researcher in his field. Teachers' actions are based solely on actual and factual problems that develop in their classes. More adri it SMP Teachers are required to be able to master the curriculum, master the material, master the method, and not least the teacher must also be able to manage the class in such a way that the learning takes place actively, innovative and fun. This school action research was conducted in SMP Muhammadiyah 5 Makassar. The timing of this classroom action research begins from 1 February 2017 to 1 June 2017, with four key steps: action planning, action execution, observation (observation), and reflection, involving teachers. Technical analysis is digchised with ANOVA method. The results of this study that by following the development training with the application of learning models, teachers generally adopt and adapt the learning models in it. Based on the results of observations of teachers (especially in cycle I), obtained the information / data that there are still teachers who have not done approach McKernan method can provide changes to the value of student learning outcomes.